PIRANTI KOHESI GRAMATIKAL KONJUNGSI DALAM KUMPULAN CERPEN HIKAYAT SUARA-SUARA KARYA TAUFIK IKRAM JAMIL - Mei Lisa Catur Putri Sari; Auzar Auzar; Charlina Charlina (Jurnal Online Mahasiswa (JOM) Bidang Keguruan dan Ilmu Pendidikan, 2020)
Abstract: This study is entitled Conjunction Grammatical Cohesion Tool in a Short Stories of Hikayat Suara-suara by Taufik Ikram Jamil. The purpose of this study is to describe the types and functions of the conjunctions contained in the collection of short stories Hikayat Suara-suara of Taufik Ikram Jamil. The benefits of this research are divided into three namely theoretical, practical and educative. The operational definition is research that leads to the conjunction cohesion markers contained in the narrative discourse text in the short story of Hikayat Suara Suara. The data of this study are sentence excerpts in the form of short stories in the data obtained by Hikayat Suara Suara. The research method used is a qualitative method that describes descriptive data. The data collection technique used is documentary study. The data validity technique uses triangulation by using two validators. Based on data analysis that has been done, found 300 data types of conjunctions and 172 data of conjunction functions contained in the collection of short stories of Hikayat Suara Suara by Taufik Ikram Jamil. on the use of elements of language rules in this case focused on focusing the short stories. Key Words: Grammatical Cohesion, Discourse Analysis, Conjunctions, Short Stories